EMPOWERMENT OF DEVELOPED SMALL MEDIUM ENTERPRISES (SMEs) TRADE OFFICE OF MEDAN CITY IN EFFORT IMPROVING WELFARE - Nurul Hasanah Lubis; Mariatul Fitri . (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2022)
The purpose of this study is how the empowerment process carried out by the Medan City Trade Office is related to the welfare of SMEs in Medan City. This research uses descriptive qualitative, purposive informant determination technique. Data was collected through observation, interviews, and documentation. The findings of this study indicate that the Medan City Trade Office has increased the involvement of SMEs in meeting and training activities. From SMEs which are included in the development of the Medan City Trade Office, they show an increase in orders, therefore SMEs get an increased turnover. This research is considered important because SMEs in Indonesia have a positive impact on people's welfare, but the challenges are very big considering that the SME market competition still has shortcomings such as marketing skills, limited information networks and aspects of capital. So the government needs to be present to empower SMEs in improving the economy, especially in the field of microeconomics.